Leonidov in the Crimea. Part 1 - Zavadovsky, Petr (project baikal, 2022)
The article considers the presently known design materials of the master plan of the South Coast of the Crimea of 1936-1937. The given analysis allows us to clarify the dating, as well as to put forward a reasonable assumption about a much greater degree of I. I. Leonidov’s participation in the authors’ team led by M. Ya. Ginzburg than it used to be considered before. This makes it possible to attribute a number of fragments of the project of the South Coast of the Crimea as I. I. Leonidov's projects.
Keywords: architecture; designing; Ivan Leonidov; South Coast of the Crimea; later constructivism